Teacher self-efficacy: teachers 'perceptions of youth and adult education (Research, Society and Development, 2020)
Teacher self-efficacy is defined by Bandura (1997) as the belief in the teaching competence to organize and accomplish requested actions in order to produce desired educational results. This research aimed to investigate teachers' perceptions concerning their beliefs about self-efficacy in the Youth and Adult Education (EJA) modality. The method used was the content analysis of Bardin (1977), the technique of word frequency analysis was applied in the sources of information inserted in Nvivo 10. 23 teachers from EJA in the region of Baixo Tocantins - PA enrolled in an extension course conducted by the Federal Institute of Pará, Campus Abaetetuba. The data were analyzed using the Cognitive Social Theory; we sought to identify quantitative indicators, resulting from the participants' answers about self-efficacy beliefs, to find the most important terms of the messages collected regarding the teachers participating in the research. The belief of self-efficacy appears as a significant factor in the process of building the professional identity of teachers.